2013
DOI: 10.31018/jans.v5i2.326
|View full text |Cite
|
Sign up to set email alerts
|

Biomethanated distillery spentwash and pressmud biocompost as sources of plant nutrients for groundnut (Arachis hypogaea L.)

Abstract: JANSBiomethanated distillery spentwash and pressmud biocompost as sources of plant nutrients for groundnut (Arachis hypogaea L.) M. Selvamurugan*, P. Doraisamy and M. Maheswari Department of Environmental Sciences, Tamil Nadu Agricultural University, Coimbatore -641003 (Tamil Nadu), INDIA *Corresponding author. E-mail: muruganens@gmail.com Received:June 23, 2013; Revised received:August 1, 2013; Accepted:August 5, 2013 Abstract: A field experiment was conducted to study the impact of biomethanated distiller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The evident impact of treatments on both elevated and diminished growth parameters is distinctly manifested in the yield and yield parameters of maize. These findings align with the results reported by Selvamurugan et al [9] and Rangaraj et al [10]. Sushil Kumar [11] and Terman et al [12] also reported an enhancement in the yield component of wheat and maize with the application of urban compost and sewage sludge.…”
Section: Resultssupporting
confidence: 91%
“…The evident impact of treatments on both elevated and diminished growth parameters is distinctly manifested in the yield and yield parameters of maize. These findings align with the results reported by Selvamurugan et al [9] and Rangaraj et al [10]. Sushil Kumar [11] and Terman et al [12] also reported an enhancement in the yield component of wheat and maize with the application of urban compost and sewage sludge.…”
Section: Resultssupporting
confidence: 91%
“…As the pressmud and distillery effluents contain plant nutrients, these could be converted into nutrient-rich organic manure. Conversion of waste products into rich organic manures not only solves the problems of disposal and pollution, but also replenishes the soils and reduces the fertilizer cost (Selvamurugan et al 2013). Although substantial work has been done on the utilization of raw pressmud in rice cultivation, the effect due to composting and enrichment of pressmud on nutrient availability, growth, yield parameters, yield and efficiency parameters of rice is very much limited.…”
Section: Introductionmentioning
confidence: 99%